Estilos de liderazgo y compromiso academico en estudiantes: Un análisis multivariado por perfiles de sexo - Pillhuaman Caña, Nelly Demetria (2025)
The study analyzed the dimensions of leadership and academic engagement in 232 university students. Through principal component analysis, two factors were identified: one that integrates transformational leadership with the dimensions of academic engagement, and another that groups transactional and laissez-faire styles. Using these factors, a k-means cluster analysis classified the students into two groups: a predominant cluster characterized by students with high academic engagement and others with transformational leadership, and another cluster displaying more indifferent styles with no connection to academic engagement. The findings will guide strategies to promote comprehensive student success.